Efecto gastroprotector del extracto total de solanum tuberosum l. var. “papa blanca” y croton lechlei l. “sangre de grado” en rattus rattus var. albinus con daño gástrico por acción del etanol - Gonzáles Llontop, Luis Felipe (2013)
He study was designed to evaluate the gastroprotective effect of total extract of Solanum tuberosum L.var. "White potato" and lechleri Croton L. "sangre de grado" in Rattus rattus var. albinus with ethanol-induced gastric damage in an experimental model used in ratas for produce gastric injury. We evaluated 35 animals divided into 07 treatment groups: control (ethanol only), problem (extracts applied) and pattern (ranitidine). Each group consisted of 05 specimens each were applied in three days fasting and doses: 200 mg / kg (Issue I), 400 mg / kg (Issue II), 200 mg / kg and 400 mg / kg (Problem III), 400 mg / kg and 800 mg / kg (Issue IV) and 100 mg / kg (Pattern) of ranitidine was the reference group to evaluate and test the effect of our treatment. After an orogastric horase administered 1 mL of ethanol to induce ulcer. 7 hours after application of the ethanol, the rats were sacrificed to perform macroscopic and microscopic evaluation and observe the degree of injury ulcerosas in different groups in the stomach of animals. Pretreatment with Solanum tuberosum L. and Croton lechleri L.administrados independently partially reduced (p <0.05) with ulcerative lesions ethanol-induced hemorrhagic necrosis, having a 20.21% and 31.26% each, while a double dose of the extract present 93, 69% show a high reduction colitis. Ranitidine showed a gastroprotective effect (p <0.05) in a 61.17% reduction of the lesion. Under the experimental conditions of our laboratory to 400 mg / Kg and 800 mg / Kg (double dose) extract used was observed better antiulcer effect.